Designing Classrooms to Maximize Student Achievement. (October 2014) - Cheryan, Sapna; Ziegler, Sianna A.; Plaut, Victoria C.; Meltzoff, Andrew N.
Improving student achievement is vital for our nation's competitiveness. Scientific research shows how the physical classroom environment influences student achievement. Two findings are key: First, the building's structural facilities profoundly influence learning. Inadequate lighting, noise, low air quality, and deficient heating in the classroom are significantly related to worse student achievement. Over half of U.S. schools have inadequate structural facilities, and students of color and lower income students are more likely to attend schools with inadequate structural facilities. Second, scientific studies reveal the unexpected importance of a classroom's symbolic features, such as objects and wall décor, in influencing student learning and achievement in that environment. Symbols inform students whether they are valued learners and belong within the classroom, with far-reaching consequences for students' educational choices and achievement. We outline policy implications of the scientific findings—noting relevant policy audiences—and specify critical features of classroom design that can improve student achievement, especially for the most vulnerable students.